First detection and molecular identification of Rickettsia massiliae, a human pathogen, in Rhipicephalus sanguineus ticks collected from Southern Taiwan. - Li-Lian Chao; Melissa Robinson; You-Fu Liang; Chien-Ming Shih (Public Library of Science (PLoS), 2022)
The Rickettsia massiliae was firstly detected and identified in Rhipicephalus sanguineus ticks infested on dogs in Taiwan. A total of 1154 Rh. sanguineus ticks collected from 158 dogs of four districts of Tainan city were examined for Rickettsia infection by nested-PCR assay targeting the citrate synthase (gltA) and outer membrane protein B (ompB) genes of Rickettsia. The Rickettsia infection was detected with a general infection rate of 2.77%, and was detected in male, female and nymphal stage with an infection rate of 2.77%, 3.22% and 1.32%, respectively. Phylogenetic relationships were analyzed by comparing the gltA and ompB sequences obtained from 9 Taiwan strains and 16 other strains representing 13 genospecies of Rickettsia. Results revealed that all Taiwan strains were genetically affiliated to the same clades of R. massiliae (spotted fever group) and R. felis (transitional group), and can be discriminated from other genospecies of Rickettsia. This study provides the first evidence of R. massiliae, a pathogenic spotted fever Rickettsia, identified in Rh. sanguineus ticks and highlight the potential threat for the regional transmission of Rickettsia infection among humans in Taiwan.